Tinjauan Kriminologis Terhadap White Collar Crime Di Indonesia - Kendry Tan (Indonesian Journal of Criminal Law, 2022)
This study aims to examine the elements that must be met by white-collar crime and the factors that cause white-collar crime, as well as preventive measures that can be taken to prevent the occurrence of white-collar crime. The research method used in conducting this research is a normative juridical research method using a conceptual approach to study white-collar crime in Indonesia. The results of this study indicate that there are elements that must be met to be categorized as a white-collar crime and there are various factors that cause white-collar crime in Indonesia. Therefore, several preventive measures are needed to prevent and hinder the occurrence of white-collar crimes in Indonesia to maintain the Indonesian economy and improve the lives of the Indonesian people.